Nonnative crayfish in Türkiye: presence records, invasion pathways, and ecological risks - Harlioglu, Muzaffer Mustafa (Tubitak Scientific & Technological Research Council Turkey, 2026)
The globalization of trade, aquaculture, and the ornamental pet industry has accelerated the transboundary movement of nonnative crayfish species, with significant ecological consequences. T & uuml;rkiye, a biodiversity-rich country bridging Europe and Asia, has increasingly become a point of concern due to the rising presence of alien crayfish taxa introduced primarily via the aquarium trade and scientific research. This study investigates the presence records of nonnative crayfish species in T & uuml;rkiye, identifies their likely introduction pathways, and outlines potential future outspread routes across the major freshwater basins of the country. Species such as Procambarus clarkii, Cherax quadricarinatus, C. albertisii, and Cambarellus patzcuarensis have been detected in commercial trade and research institutions in & Idot;zmir, & Idot;stanbul, Ankara, and Adana. While established wild populations have not yet been confirmed, the continued import, sale, and handling of high-risk species without adequate regulation suggests a high likelihood of future invasions. The ecological characteristics of these crayfish, including high reproductive rates, broad environmental tolerances, and disease-carrying potential, make them particularly dangerous once released into natural ecosystems. Our analysis identifies Western Anatolia, particularly & Idot;zmir, as a key introduction hub, with plausible spread routes extending northwest to the Marmara Region, east to Central Anatolia, and south toward the Mediterranean watershed. The review emphasizes the need for immediate preventive action, including the development of species-specific legislation, enhanced surveillance through molecular tools, public education campaigns, and stricter control over the pet and aquaculture trades. Without such measures, T & uuml;rkiye risks replicating the ecological and economic disruptions experienced by other European nations affected by invasive crayfish. The review also highlights that T & uuml;rkiye's geographical location, coupled with its commercial fishery ties to Iran, Azerbaijan, Georgia, and Armenia, increases the risk of invasive alien crayfish species spreading beyond T & uuml;rkiye's borders due to their presence in urban areas and widespread online ornamental trade, posing a broader threat to global freshwater ecosystems.
Keywords: Crayfish distribution; ecological risk; future invasion routes; invasive species; pet trade introduction; Procambarus clarkii